2011
DOI: 10.1080/10615806.2011.558191
|View full text |Cite
|
Sign up to set email alerts
|

Crossover of job demands and emotional exhaustion within teams: a longitudinal multilevel study

Abstract: This study investigated the crossover of job demands and emotional exhaustion among team members and the moderating effect of cohesiveness and social support on this process. Participants were 310 employees of an employment agency in the Netherlands, working in one of 100 teams. Multilevel analysis using a longitudinal design did not reveal a main effect of crossover. However, consistent with the study's hypotheses, the results showed a moderating effect of team cohesiveness and social support. We detected cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 1 publication
4
59
1
Order By: Relevance
“…In a study by Totterdell et al (1998), the link between team-level mood and individual mood (positive and negative) was strongest for those nurses who perceived the team climate as positive. In a similar vein, Westman et al (2011) found in their study that exhaustion crossed over from teams to individual employees only when teams had high levels of cohesiveness or collegial social support. However, to our knowledge, no studies have examined the crossover of exhaustion (burnout) among working dyads in health care or considered how frequent and positive interpersonal relationships may affect the crossover effect.…”
Section: Moderators Of the Crossover Effectmentioning
confidence: 79%
See 2 more Smart Citations
“…In a study by Totterdell et al (1998), the link between team-level mood and individual mood (positive and negative) was strongest for those nurses who perceived the team climate as positive. In a similar vein, Westman et al (2011) found in their study that exhaustion crossed over from teams to individual employees only when teams had high levels of cohesiveness or collegial social support. However, to our knowledge, no studies have examined the crossover of exhaustion (burnout) among working dyads in health care or considered how frequent and positive interpersonal relationships may affect the crossover effect.…”
Section: Moderators Of the Crossover Effectmentioning
confidence: 79%
“…This is because positive interrelationships make the receiver more open-minded and receptive to the sender's feelings, which in turn may lead to either a conscious or unconscious empathic reaction in the receiver, thus enabling the crossover (Barsade, 2002). Therefore, when a dental nurse, for example, feels that his or her exhausted partner, a dentist, is acting kindly towards him or her and showing positive gestures, this friendliness may create openness and empathy in the nurse and hence enable the crossover of exhaustion from the dentist to the dental nurse in regular and intensive collaboration (see also Westman et al, 2011). Thus, we hypothesize that both frequent and positive collaboration is needed for the crossover of exhaustion.…”
Section: Moderators Of the Crossover Effectmentioning
confidence: 96%
See 1 more Smart Citation
“…Such mechanisms operate as a school-level "emergent" phenomenon (i.e., a phenomenon that "originates in the cognition, affect, behaviors, or other characteristics of individuals, is amplified by their interactions, and manifests as a higher-level, collective phenomenon"; Kozlowski & Klein, 2000) rather than as a student-level mechanism. Organizational theory provides numerous examples of how organizational climate, measured at an individual level and aggregated to a higher level as a property of the whole organization, impacts individual members' performance (e.g., Westman, Bakker, Roziner, & Sonnentag, 2011).…”
Section: Study Assumptionsmentioning
confidence: 99%
“…In recent years interpersonal processes like emotional contagion or crossover of burnout at work have been gaining more and more interest. They include inter-individual transmission of feelings and attitudes from one employee to another and, consequently, the convergence of emotion [34] .…”
Section: Emotions and Their Outcomes In Nurse Work Environmentmentioning
confidence: 99%